Talkpod Program Broadcasting Diversification Program on Net Tv Through Digital Platform - Raudhatul Fitri; Rustim; Dynia Fitri; FX. Yatno Karyadi (Kirana Publisher (KNPub), 2024)
This research is to reveal that broadcasting diversification is an important strategy for television stations in facing the development of broadcasting technology platforms and changes in social media consumption patterns of android-based communities. The